Experimental validation of a performance curve using a Tetris game - Charelle Bottenheft; Eric L. Groen; Jan B.F. van Erp (BMC Psychology)
Abstract Background Theoretical models on cognitive performance predict that performance breaks down at higher task load levels, because of limiting cognitive resources. Experimental validation of these models is scarce, and they often don’t accommodate effects of invested effort and/or stressors. We experimentally measured a performance-curve as a function of increasing task load using a Tetris game. In addition, we investigated if performance breakdown occurs at different task load levels in the presence of a stressor. We hypothesized that an external stressor would shift the performance-curve to the left (i.e. lower task load levels) while maintaining the same form. Methods Twenty-one participants completed one training day and two test days (data collection: 2023). During training, an individual break-off level on the Tetris game was determined with a staircase method. Subsequently, on the two test days participants played nine predetermined task load levels on and around their break-off level. On one test day they were exposed to heat load, and on the other test day to room temperatures. Task load levels and test room temperature were counterbalanced. Results The results show that a sigmoid model is successful in fitting the performance decline pattern at high task load levels. Heat load did not seem to affect the parameters of the sigmoid curves. Conclusions This study provides experimental evidence for a performance-curve as a function of increasing task load, resembling the right side of the classic inverted U-curve. Contrary to our expectation, we did not find evidence for a stressor-induced shift of the individual performance-curve, presumably because the increase in body core temperature (TC) was insufficient to affect cognitive performance. Tetris seems a suitable tool to reproduce the performance-curve, and to perform research into factors that may affect the relation between mental effort and performance.